Growth performance and nutrient composition of Bufo maculata (Linneaus) tadpole fed different practical diets as fish meal substitute - Sogbesan, Olukayode Amos; Ugwumba, Alda Adhia Alex (Advances in Aquaculture and Fisheries Management, 2021)
One thousand and one hundred (1,100) Bufo maculata tadpoles of weight range 0.03 -0.05 g (mean = 0.04 ± 0.008 g) and length range, 1.2 - 1.6 cm (mean = 1.4 ± 0.018 cm) were collected from the breeding tanks using scoop net and stocked into the outdoor concrete culture tanks coded according to the experimental diet at the rate of one hundred and twenty tadpoles of known weights and lengths per tanks and cultured for 84 days. The growth performances, feed utilization and nutrient composition of the tadpoles (B. maculata) fed three experimental diets namely live zooplankton alone (D1), 40% crude protein National Institute for Freshwater Fisheries Research (NIFFR) crumb diet alone (D2) and mixed diet (50% live zooplankton and 50% of dry 40% crude protein NIFFR crumb (D3) were studied. They were harvested after culture and processed into meal. The best mean weight gain (3.65 g/tadpole), specific growth rate (2.34%/day) and feed conversion ratio (2.05) were from tadpole fed mixed diets.